Digitalization Learning Era: Electronic Module as An Interactive Learning Material - Amartya Angela; Dewi Nopita; Rona Elfiza (Juliet, 2023)
The goal of this study was to create an electronic module that would provide an engaging learning tool for eighth-grade students which primarily focused on recount text. This study was carried out in SMPN 2 Tanjungpinang during the second semester of the academic year 2022/2023, specifically in class 8.1, which had 35 students. Additionally, the research and development approach used in this study was a 4D model that included three stages: define, design, and develop. In order to obtain the data, the researcher utilized questionnaires, including the validation questionnaire for experts and the practicality questionnaire for students. The data analysis revealed that the studentsâ€™ practicality score was 85%, which was classified as â€œVery Practical,â€ and the material and media validation score was 98%, which was classified as â€œVery Valid.â€ These findings support the hypothesis that the product developed for this study was valid, practical, and eligible to be used in the learning process.